Investigating fine-scale population dynamics in the threatened Cape Dwarf eelgrass, Zostera capensis, using RADseq - Jackson, Megan Jane (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2021.